Adaptive unified continuum FEM modeling of a 3D FSI benchmark problem. (11th April 2017) - Jansson, Johan; Degirmenci, Niyazi Cem; Hoffman, Johan
Abstract: In this paper, we address a 3D fluid‐structure interaction benchmark problem that represents important characteristics of biomedical modeling. We present a goal‐oriented adaptive finite element methodology for incompressible fluid‐structure interaction based on a streamline diffusion–type stabilization of the balance equations for mass and momentum for the entire continuum in the domain, which is implemented in the Unicorn/FEniCS software framework. A phase marker function and its corresponding transport equation are introduced to select the constitutive law, where the mesh tracks the discontinuous fluid‐structure interface. This results in a unified simulation method for fluids and structures. We present detailed results for the benchmark problem compared with experiments, together with a mesh convergence study. Abstract : We address a 3D fluid‐structure interaction benchmark problem representing important characteristics of biomedical modeling. We present a goal‐oriented adaptive finite element methodology for incompressible fluid‐structure interaction based on a stabilization of the balance equations for the entire continuum in the domain, with a discontinuous phase marker selecting constitutive law tracked by the mesh, which is implemented in the Unicorn/FEniCS framework. We present detailed results for the benchmark problem compared with experiments, together with a mesh convergence study.